ANALISIS BEBERAPA HARA MAKRO PADA TANAMAN JAMBU KRISTAL PADA DESA RASAU JAYA, KABUPATEN KUBURAYA - Indrawati, Urai Suci Yulies Vitri; Agustine, Leony; Febrianti, Ristha (Fakultas Pertanian, Universitas Janabadra, 2024)
Aluvial soil is soil that has low productivity because the pH is acidic, contains pyrite, and is poor in macro and macro nutrients. Rasau Jaya Tiga Village, Kubu Raya Regency is one of the centers for Crystal Guava plants, where there are differences in the productivity of Crystal Guava plants between one plantation and another. The aim of this research is to test the status of the nutrients N, P, K at 2 locations of Crystal Guava plantations, provide fertilizer suggestions at 2 research locations. This research will be carried out in a crystal guava plantation owned by 2 farmers, which covers an area of 1 Ha with a plant age of 2 years. Soil sample analysis was carried out at the Soil Chemistry and Fertility Laboratory, Faculty of Agriculture, Tanjungpura University. The research will be conducted in January–July 2023 for 6 months starting from preparation to presenting the results. From the research results, the nutrient status of the two fields showed that the status of the Nitrogen element was included in the very high criteria, the status of the Phosphorus element was included in the very high criteria and the status of the Potassium element was included in the low criteria. Fertilization suggestions are only for K, namely at location 1 as much as 0.25 kg/plant, and location 2 as much as 0.75 kg/plant. Key words: Alluvial Soil, Crystal guava. INTISARITanah Aluvial adalah tanah yang memiliki produktivitas yang rendah karena pH yang masam, mengandung pirit, miskin unsur hara makro dan makro. Desa Rasau Jaya Tiga Kabupaten Kubu Raya merupakan salah satu sentra tanaman Jambu Kristal, dimana terdapat perbedaan produktivitas tanaman jambu kristal antara kebun satu dan yang lainnya.Tujuan dari penelitian ini adalah menguji status unsur hara N, P, K pada 2 lokasi kebun jambu kristal, memberikan saran pemupukan di 2 lokasi penelitian. Penelitian ini akan dilaksanakan di kebun jambu kristal milik 2 petani, yang luas nya 1 Ha dengan usia tanaman 2 tahun. Analisis sampel tanah dilakukan di Laboratorium Kimia dan Kesuburan Tanah Fakultas Pertanian Universitas Tanjungpura. Penelitian akan dilakukan pada bulan Januari–Juli 2023 selama 6 bulan dimulai dari persiapan sampai penyajian hasil. Dari hasil penelitian, status hara pada kedua lahan di dapatkan bahwa status unsur Nitrogen termasuk dalam kriteria sangat tinggi, status unsur Fosfor termasuk dalam kriteria sangat tinggi dan status unsur Kalium termasuk dalam kriteria rendah. Saran pemupukan hanya untuk K, yaitu pada lokasi 1 sebanyak 0,25 kg/tanaman, dan lokasi 2 sebanyak 0,75 kg/tanaman. Kata kunci: Tanah Aluvial, Jambu kristal